Primary ovarian neuroendocrine tumor arising in association with a mature cystic teratoma: A case report - Nicolas M. Orsi; Mini Menon (Elsevier, 2016)
Primary ovarian carcinoid tumors are exceptionally rare entities accounting for approximately 0.1% of all ovarian neoplasms. This report describes a primary ovarian neuroendocrine tumor arising in association with a mature cystic teratoma in a 65 year-old woman. Macroscopically, the unilateral adnexal tumor was composed of cystic, solid and mucinous elements which resolved into a dual component lesion histologically. The majority of the tumor displayed an organoid architecture with mild to moderate pleomorphism and no discernible mitotic activity, while approximately 10% consisted of sheets and groups of cells with highly pleomorphic nuclei, necrosis and occasional mitoses. Features of a mature cystic teratoma were seen very focally. Immunohistochemistry revealed strong, diffuse positivity for CD56 and synaptophysin. Chromogranin immunonegativity was noted and there was an absence of nuclear β-catenin accumulation. Ki-67 index was 10-12%. Although there is no established diagnostic framework for primary ovarian carcinoid tumors, this case was diagnosed as a well-differentiated neuroendocrine tumor, Grade 2 (intermediate grade), arising in association with a mature cystic teratoma/dermoid cyst. This case highlights the need to develop ovarian diagnostic criteria in this area.